EFEKTIFITAS PELAKSANAAN PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SEKOLAH (STUDI PADA SMA NEGERI SE KABUPATEN PONOROGO) - YUDHA PRATAMA, YONA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education is the education that cannot be underestimated because it has important role for the students’ future. The quality of it shown by the learning effectiveness that can be seen from the preparation, learning realization, and the students’ activities during the learning process. Besides that, it can be observed from the result, willingness, method, and cooperation from the students’ perspective. However, that fact is that the physical education is underestimated and the students’ fail to understand the learning material. Because of the importance of physical education, a teacher has to be creative and innovative in order to create conducive and effective learning atmosphere until the learning materials become attractive, not boring, and the learning objectives can be achivied.This study aims to now how the effectiveness of the realization of physical education learning in schools. The method used in this study is descriptive quantitative.The result of this study showed that effectiveness of the realization of physical education learning in schools (Study in Ponorogo state high school) belonging to good category by the students’ formative questionnaire average score of 4. The average score of the learning effectiveness based on the observation is 61,37% and can be categorized as good.Based on the whole result of this study, it can be concluded that the effectiveness of the realization of physical education learning in Ponorogo state high schools included is included into good category. Keywords : interest, students, sports extracurricular activities